The trace amine-associated receptor 1 modulates methamphetamine's neurochemical and behavioral effects - Cotter, Rachel; Pei, Yue; Mus, Liudmila; Harmeier, Anja; Gainetdinov, Raul R.; Hoener, Marius C.; Canales, Juan J. (Frontiers in Neuroscience, 2015)
The newly discovered trace amine-associated receptor 1 (TAAR1) has the ability to regulate both dopamine function and psychostimulant action. Here, we tested in rats the ability of RO5203648, a selective TAAR1 partial agonist, to modulate the physiological and behavioural effects of methamphetamine (METH). In experiment 1, RO5203468 dose- and time-dependently altered METH-induced locomotor activity, manifested as an early attenuation followed by a late potentiation of METH’s stimulating effects. In experiment 2, rats received a 14-day treatment regimen during which RO5203648 was co-administered with METH. RO5203648 dose-dependently attenuated METH-stimulated hyperactivity, with the effects becoming more apparent as the treatments progressed. After chronic exposure and 3-day withdrawal, rats were tested for locomotor sensitization. RO5203648 administration during the sensitizing phase prevented the development of METH sensitization. However, RO5203648, at the high dose, cross-sensitized with METH. In experiment 3, RO5203648 dose-dependently blocked METH self-administration without affecting operant responding maintained by sucrose, and exhibited lack of reinforcing efficacy when tested as a METH’s substitute. Neurochemical data showed that RO5203648 did not affect METH-mediated DA efflux and uptake inhibition in striatal synaptosomes. In vivo, however, RO5203648 was able to transiently inhibit METH-induced accumulation of extracellular DA levels in the nucleus accumbens. Taken together, these data highlight the significant potential of TAAR1 to modulate METH’s neurochemical and behavioural effects.